Um novo olhar no Ensino de Física nos cursos de engenharia na Amazônia - Souza, Maud Rejane de Castro e (2011)
This dissertation consists of a new proposal for teaching physics, whose aim is to analyze the effect of an innovative methodology applied in physics I, in a class of Engineering, University Nilton Lins, where the emphasis is on dialogue, rescue know the students. Looking subsumers needed to discover a meaningful learning, we use the problem-solving, engineeringrelated with the daily lives of students, in order to arouse the same interest in the discipline and demystify physics as a difficult subject and without context. Even through activities in experimental physics lab, where students made observations, collection, interpretation and analysis of data in bursts, thus allowing the development of attitudes towards the exercise of democratic practice and exchange of experiences. The results showed that the proposed methodological improvements took effect and can be used along with other proposals to strengthen the teaching and learning of physics in the Amazon.